Impact of Information Technology Infrastructure Flexibility on Mergers and Acquisitions1 - Benitez, Jose; Ray, Gautam; Henseler, Jörg (MIS Quarterly, 2018)
Although mergers and acquisitions (M&A) are a common strategy to reduce costs and pursue growth, the variance in returns from M&A is very high. This research examines how information technology (IT) infrastructure flexibility affects M&A. We use a combination of secondary as well as matched-pair survey data from 100 midsize firms in Spain to investigate this relationship. The empirical analysis suggests that IT infrastructure flexibility affects M&A through two key pathways: (1) a flexible IT infrastructure facilitates the development of business flexibility that provides the responsiveness to seize M&A opportunities and make acquisitions, and (2) a flexible IT infrastructure facilitates the development of post-M&A IT integration capability that provides the control to integrate the IT and business resources of the acquired firm and realize the economic benefits from M&A.